Effect of bioelectrical impedance technology on the prognosis of dialysis patients: a meta-analysis of randomized controlled trials - Kaibi Yang; Shujun Pan; Nan Yang; Juan Wu; Yueming Liu; Qiang He (Renal Failure)
Managing patient ‘dry weight’ according to clinical standards has deficiencies. Research has focused on the effectiveness of using bioelectrical impedance technology for fluid management in dialysis patients. Whether bioelectrical impedance monitoring can improve dialysis patients prognoses remain controversial. We performed a meta-analysis of randomized controlled trials to determine whether bioelectrical impedance was effective in improving dialysis patients prognoses. The primary outcome was all-cause mortality (13.6 ± 9.1 months). Secondary outcomes were left ventricular mass index (LVMI), arterial stiffness assessed using Pulse Wave Velocity (PWV), and N-terminal brain natriuretic peptide precursor (NT-proBNP). Of 4,641 citations retrieved, we identified 15 eligible trials involving 2763 patients divided into experimental (n = 1386) and control (n = 1377) groups. In 14 studies with mortality data, the meta-analysis showed that bioelectrical impedance intervention reduced the risk of all-cause mortality (rate ratios [RR]: 0.71; 95% confidence interval [CI]: 0.51, 0.99; p = .05; I2 = 1%). Subgroup analysis of patients on hemodialysis (RR: 0.72; 95% CI: 0.42, 1.22; p = .22) and peritoneal dialysis (RR: 0.62; 95% CI: 0.35, 1.07; p = .08) showed no significant mortality difference between intervention and control groups. It reduced the risk of all-cause mortality in the Asian population (RR: 0.52; p = .02), and reduced NT-proBNP (mean difference [MD]: −1495.73; p = 0.002; I2=0%) and PWV (MD: −1.55; p = .01; I2=89%). Bioelectrical impedance intervention reduced the LVMI in hemodialysis patients (MD: −12.69; p < .0001; I2=0%). Our analysis shows that in dialysis patients, bioelectrical impedance technology intervention could reduce, but not eliminate, the risk of all-cause mortality. Overall, this technology can improve the prognosis of dialysis patients.